2014 IEEE Conference on Energy Conversion (CENCON) 2014
DOI: 10.1109/cencon.2014.6967469
|View full text |Cite
|
Sign up to set email alerts
|

Energy and power control strategy for battery electric vehicle with supercapacitors

Abstract: This paper presents a new energy and power management control strategy for battery electric vehicle (BEV) with supercapacitors (SCs) based on speed command and acceleration estimation. The purpose of the control strategy is to increase the capability of regenerative braking energy capturing and to improve DC bus voltage regulation. The control strategy uses cascade voltage and current control of SCs. The voltage and current references are calculated based on the speed command and acceleration including the pow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…The SC and LIB provided the desired current to the load, which was controlled using an Arduino microcontroller. A bidirectional converter was used in boost mode, whereas discharging and buck mode were used in charging mode [42]. The output voltage of SC (V SC ) varied according to its state of charge, while the battery voltage (V bat ) remained almost constant.…”
Section: Overview Of the Proposed Methodologymentioning
confidence: 99%
“…The SC and LIB provided the desired current to the load, which was controlled using an Arduino microcontroller. A bidirectional converter was used in boost mode, whereas discharging and buck mode were used in charging mode [42]. The output voltage of SC (V SC ) varied according to its state of charge, while the battery voltage (V bat ) remained almost constant.…”
Section: Overview Of the Proposed Methodologymentioning
confidence: 99%
“…It has to be stated that, as discussed in [9], a low-rate charge or discharge cannot be considered as OCV or pseudo-OCV curves as they are not independent of the regime. The pseudo-OCV curve can be calculated by averaging the low-rate charge and discharge curves [9,41,42]. This method is usually accurate, but it is highly recommended to check the validity of the results.…”
Section: Reference Performance Testmentioning
confidence: 99%
“…The low-rate cycle provides thermodynamic information; while the high-rate cycle reveals kinetic information. Since voltage variations are minute, derivatives are recommended, either incremental capacity (IC, dQ/dV = f(V)) [9,42,45,[47][48][49] or differential voltage (DV, dV/dQ = f(Q)) [50][51][52]. Interested readers should refer to [9] for a complete discussion of the advantages and disadvantages of both these electrochemical voltage spectroscopies (EVS).…”
Section: Reference Performance Testmentioning
confidence: 99%
“…Combination of thebattery and supercapacitor has integral characteristics and gives an astounding arrangement that can cover a wide scope of intensity and vitality necessities [12]. Accordingly, upgrade of intensity quality utilizing batteries and supercapacitors is effectively sought after in the field of sustainable power source and it was shown that this hybridization has lower battery costs, an overall increment in battery life and higher efficiency which may not be fulfilled by the single storage device [13], [14] hence the hybridization was grown effectively in numerous applications like battery electric vehicle, hybrid electric vehicle and uninterruptible power supply as presented in [15]- [17]. In ESSs applications, they ordinarily use SC terminal voltage as the criticism of regulator to accomplish constant control for the SC [18].…”
Section: Introductionmentioning
confidence: 99%